Implementasi Corporate Social Responsibility dan Implikasinya dalam Perspektif Teori Stakeholder (Studi pada Perusahaan Tekstil dan Produk Tekstil di Jawa Tengah) - Edy Rahardja; Djumilah Zain; Ubud Salim; Mintarti Rahayu (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
CSR implementation and impact on social and financial performance have been long debated. This study used 108 samples of textile and its products companies in Central Java Province employing Stratified Random Sampling method based ISO certification ownership. Data analysis used Structural Equation Modelling (SEM), utilized AMOS 16.0. Prior to hypothesis examination, data validity and reliability as well as model appropriateness were examined. This study suggested the hypothesis to examine the relationship among corporate stakeholder strategy, social capital, CSR implementation, corporate social performance, and corporate financial performance as research variables. The result of the study showed that: corporate stakeholder strategy intensity may improve social capital building; social capital as an unique characteristics of firms may stimulate CSR implementation better and may achieve corporate social performance better; commitment and consistency of CSR implementation are likely to make corporate financial performance better; and there is no relationship between corporate social performance and corporate financial performance.Keywords: social capital, CSR, stakeholder theory, corporate social performance and corporate financial performance